SISTEM INFORMASI KOPERASI SIMPAN PINJAM KESRA KANTOR KECAMATAN NGOMBOL, PURWOREJO - , HIJRIYANI NUGROHO DWI SAPUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
\"Kesra\" Cooperative, Ngombol District Office is a cooperative that gives savings and loan service for its members. Currently, the processing of saving and loan database, the processing of data members and the calculation of SHU in the cooperative is still done manually. Savings and loans data is recorded in the book and in the Calculation of Interest. Loan service & SHU calculation also using manual calculation tools. In this manual process, the errors in recording and calculation, data duplication, or missing archive is frequently happens. The office have a hard time with all this problem. Human memory limitation also create misunderstanding between cooperative member on loan payment. Therefore, there is a need of system that can store and process data automatically. Based on that problem, Kesra Cooperative Savings and Loans Information System is built using PHP programming language with CodeIgniter framework and MySQL database. Kesra Cooperative Savings and Loans Information System are also made with jQuery javascript framework. Kesra Cooperative Savings and Loans Information System is able to process savings and loan data. This system can recapitalize and process officer data, member data, storage data, loan data, expenditure data, and is also capable of calculating interest on loans, deposit services, and SHU. Kesra Cooperative Savings and Loans Information System can produce financial report in the form of tables and graphs.